Avoiding short circuits from zinc metal dendrites in anode by backside-plating configuration - Shougo Higashi (Nature Portfolio, 2016)
Zinc-based aqueous battery chemistries allow for attractive cost and energy densities, but are susceptible to zinc dendrite formation during plating and internal shorting. Here, the authors show that by plating only on the side away from the counter-electrode, internal shorts can be circumvented.